2002
DOI: 10.1007/bf03218328
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(vinyl alcohol-b-styrene)via atom transfer radical polymerization and saponification

Abstract: Poly(vinyl alcohol-b-styrene) (poly(VA-b-St)) diblock copolymer containing high syndiotactic poly (vinyl alcohol) (PVA) was synthesized by the saponification of poly(vinyl pivalate-b-styrene) (poly(VPi-b-St)). For the block copolymer, poly(vinyl pivalate) (PVPi) with trichloromethyl end group was obtained via telomerization of vinyl pivalate with carbon tetrachloride as a telogen and 2,2-azobisisobutyronitrile (AIBN) as an initiator. Then resulting poly(vinyl pivalate) with trichloromethyl end group was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Poly(VA-b-St) block copolymers containing PVA with different tacticity were prepared as described in our previous papers [20,21]. The molecular characteristics of block copolymer are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Poly(VA-b-St) block copolymers containing PVA with different tacticity were prepared as described in our previous papers [20,21]. The molecular characteristics of block copolymer are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The small peak (g) at 0.8 ppm was attributed to the methyl protons of the initiator. The signal (b) at 2.1 ppm corresponded to the methylene protons of the monomer unit [25]. The resonance (a) at approximately 5.85 ppm attributed to the methine proton adjacent to terminal bromine at the x-end, which indicates the preservation of end group [46].…”
Section: End Group Analysismentioning
confidence: 97%
“…Later, these copolymers were employed as stabilizers in the dispersion polymerization of N-vinyl pyrrolidone, which yielded polymers with high conversion and molecular weight [15,28]. In addition, Li et al [25,47] reported the synthesis of poly(VPi-b-St) by ATRP using VPi telomer as a macroinitiator, where the telomer was prepared by radical telomerization of VPi using carbon tetrachloride. The structure of PVPi-b-PVAc synthesized in scCO 2 was confirmed by 1 H NMR (Fig.…”
Section: Chain Extension Of Pvpimentioning
confidence: 98%
See 1 more Smart Citation
“…CMC, which is a measured physical parameter of micelles, refers to their thermodynamic stability. 39 The CMC of the block copolymers was determined by a fluorescence technique with pyrene as the probe. 40 Figure 1D shows the intensity ratios (I 1 :I 3 ) of pyrene monomer emission spectra versus the concentrations of micelles and micelles containing NaC (CMs), respectively.…”
Section: Determination Of Critical Micelle Concentrationmentioning
confidence: 99%